The birthday of first Hungarian Rebuplic: Budapest, November 16, 1918. - Vizi, László Tamás (Acta Scientiarum Socialium, 2018)
With the date of 16 November 1918, most people associate to the proclamation of the first Republic of Hungary at the Parliament, and certainly, the name of Mihály Károlyi comes to their minds.This is no coincidence, as that was undoubtedly the most massive event of the day. However, the relevant events in the sense of public law did not take place in the square in front of the Parlament, but inside its building. This relevant event was the last session and dissolution of the Parlament, that operated continously since 1910, and last session and closure of the Upper House, that resulted the end of the parliamentary procedure. On the same day, during the session of the Council of Ministers, the Government decided on the name of the country as well. The plenum defined the state form as People’s Republic. The Grand National Council, including the delegates of the county national councils, proclaimed the Republic during its first session in the Parlament’s House of Cups and adopted its first people's resolutions. At the same time declared that October 31 and November 16 would be national holidays.
Keywords: Great War (1914‒1918); history of Central-Europe; History of Hungarian Kingdom at 1918